Whole-Brain Perfusion CT Using a Toggling Table Technique to Predict Final Infarct Volume in Acute Ischemic Stroke - Schrader, I.; Wilk, D.; Jansen, O.; Riedel, C. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To evaluate how accurately final infarct volume in acute ischemic stroke can be predicted with perfusion CT (PCT) using a 64-MDCT unit and the toggling table technique.Materials and Methods: Retrospective analysis of 89 patients with acute ischemic stroke who underwent CCT, CT angiography (CTA) and PCT using the “toggling table” technique within the first three hours after symptom onset. In patients with successful thrombolytic therapy (n = 48) and in those without effective thrombolytic therapy (n = 41), the infarct volume and the volume of the penumbra on PCT were compared to the infarct size on follow-up images (CT or MRI) performed within 8 days. The feasibility of complete infarct volume prediction by 8 cm cranio-caudal coverage was evaluated.Results: The correlation between the volume of hypoperfusion on PCT defined by cerebral blood volume reduction and final infarct volume was strongest in patients with successful thrombolytic therapy with underestimation of the definite infarct volume by 8.5 ml on average. The CBV map had the greatest prognostic value. In patients without successful thrombolytic therapy, the final infarct volume was overestimated by 12.1 ml compared to the MTT map on PCT. All infarcts were detected completely. There were no false-positive or false-negative results.Conclusion: Using PCT and the “toggling table” technique in acute stroke patients is helpful for the rapid and accurate quantification of the minimal final infarct and is therefore a prognostic parameter which has to be evaluated in further studies to assess its impact on therapeutic decision.Key Points:Citation Format:
Keywords: CT perfusion; stroke; toggling table; MDCT